Pornography Use and Loneliness in Adolescents - Mestre-Bach, Gemma; Villena, Alejandro; Granero, Roser; Serrano, Gabriel; Fernandez-Aranda, Fernando; Jiménez-Murcia, Susana; Chiclana Actis, Carlos (International Journal of Sexual Health, 2022)
This presentation will focus on the use of pornography in adolescents. This topic deserves special attention because adolescents are a population especially vulnerable to pornographic content. Current findings will be discussed regarding the association between adolescent pornography use and multiple factors (sexual behaviors, risk behaviors, problematic pornography use, and relationships with peers and family members, among others). Subsequently, we will present the results of our study.
Keywords: pornography; loneliness; adolescents; JCR